Weight-Based Victimization and Physical Activity Among Adolescents With Overweight or Obesity: A Scoping Review of Quantitative and Qualitative Evidence - Skogen, Ingeborg B.; Båtevik, Finn Ove; Krumsvik, Rune Johan; Høydal, Kjetil L. (Frontiers in Sports and Active Living, 2022)
Background Increased physical activity engagement plays a vital role in preventing and treating overweight or obesity in children and adolescents. Research has found that adolescents who are overweight or obese tend to participate in less physical activity than adolescents of average weight. Weight-based victimization (victimization related to weight or body size) is highly prevalent in adolescence and seems to be a factor that might negatively impact engagement in physical activity. This scoping review's objective was to identify the nature and extent of research evidence on links between weight-based victimization and physical activity among community-based or primary health care samples of adolescents who are overweight or obese. Methods Following established scoping review methods, we searched electronic databases PubMed, Web of science, SportDiscuss, and Cinahl from 23 Nov 2020 to 02 Dec 2020. Published studies with community-based or primary health care samples of adolescents who were overweight or obese (aged 13–18 years, Iso-BMI ≥ 25, i.e., age and gender specific percentiles based on specified cut-off value for overweight and obesity) and that were peer-reviewed and published were included in the analysis. Data from the included studies were put into a table and analyzed descriptively and numerically in terms of the extent and nature of the studies. Results After full text review, 12 articles were included, equally distributed in the qualitative and quantitative paradigm. There was a homogeneity of the research designs applied. Articles revealed high frequency of weight-based victimization. Among quantitative studies the reported links between weight-based victimization and physical activity were somewhat mixed, with three studies reporting weight-based victimization to negatively impact physical activity, while three studies report no significant impact. Qualitative studies reported experiences of teasing and bullying by peers, humiliation, and feelings of insecurity about appearance as barriers to engagement in physical activity. Conclusion The empirical evidence on the links between weight-based victimization and physical activity among community-based or primary-health care samples of adolescents who are overweight or obese is sparse. The results revealed a high presence of weight-based victimization in physical activity which seems to act as barriers for activity engagement. There is a need for more research to advance the understanding of the links between weight-based victimization and physical activity among community-based or primary-health care samples of adolescents who are overweight or obese.